SWOT Analysis as a Company Strategy for Business Competition - Rachmat Irawan, Cahyo (Siber Journal of Transportation and Logistics, 2024)
SWOT analysis is an important strategic tool for companies to understand their position in the market through identifying strengths, weaknesses, opportunities and threats. Using this analysis, companies can develop strategies that capitalize on strengths and opportunities while addressing weaknesses and threats. This helps increase the company's competitiveness and performance in facing ever-changing business dynamics.